Thoracic dorsal root ganglion stimulation reduces acute myocardial ischemia induced ventricular arrhythmias - Yuki Kuwabara; Kimberly Howard-Quijano; Kimberly Howard-Quijano; Siamak Salavatian; Siamak Salavatian; Tomoki Yamaguchi; Samir Saba; Aman Mahajan; Aman Mahajan (Frontiers in Neuroscience, 2023)
BackgroundDorsal root ganglion stimulation (DRGS) may serve as a novel neuromodulation strategy to reduce cardiac sympathoexcitation and ventricular excitability.ObjectiveIn this pre-clinical study, we investigated the effectiveness of DRGS on reducing ventricular arrhythmias and modulating cardiac sympathetic hyperactivity caused by myocardial ischemia.MethodsTwenty-three Yorkshire pigs were randomized to two groups, which was control LAD ischemia-reperfusion (CONTROL) or LAD ischemia-reperfusion + DRGS (DRGS) group. In the DRGS group (n = 10), high-frequency stimulation (1 kHz) at the second thoracic level (T2) was initiated 30 min before ischemia and continued throughout 1 h of ischemia and 2 h of reperfusion. Cardiac electrophysiological mapping and Ventricular Arrhythmia Score (VAS) were assessed, along with evaluation of cFos expression and apoptosis in the T2 spinal cord and DRG.ResultsDRGS decreased the magnitude of activation recovery interval (ARI) shortening in the ischemic region (CONTROL: −201 ± 9.8 ms, DRGS: −170 ± 9.4 ms, p = 0.0373) and decreased global dispersion of repolarization (DOR) at 30 min of myocardial ischemia (CONTROL: 9546 ± 763 ms2, DRGS: 6491 ± 636 ms2, p = 0.0076). DRGS also decreased ventricular arrhythmias (VAS–CONTROL: 8.9 ± 1.1, DRGS: 6.3 ± 1.0, p = 0.038). Immunohistochemistry studies showed that DRGS decreased % cFos with NeuN expression in the T2 spinal cord (p = 0.048) and the number of apoptotic cells in the DRG (p = 0.0084).ConclusionDRGS reduced the burden of myocardial ischemia-induced cardiac sympathoexcitation and has a potential to be a novel treatment option to reduce arrhythmogenesis.